دراسة تأثير اللاتانوبروست موضعياً على ثخانة القرنية المركزية عند مرضى الزرق البدئي مفتوح الزاوية - يوسف, حبيب; رجب, محمود; قاسم, منار (Latakia University Journal -Medical Sciences Series, 2018)
Purpose: To study the effect of topical Latanoprost on central corneal thickness in patients with primary open glaucoma, and to see if it would be necessary to measure central corneal thickness values regularly in those patients. Patients and methods: This research included 19 patients who visited the ophthalmology clinic at Tishreen University Hospital and former Al-Assad University Hospital in Lattakia in the period between January 2016 and December 2016. There were 11 males and 8 females. Mean age was 56.1 + 5.08 and ages ranged between 49 and 66 years. After diagnosing glaucoma in only one eye, each patient was evaluated with an inclusive eye examination in addition to Schirmer test and measuring central corneal thickness CCT for both eyes. Latanoprost eye drop 0.005% was prescribed for the diseased eye only. Each patient was followed up after 1, 3, and 6 months. Results: There was a significant reduction in mean CCT in the case group, from 536.52 + 17.49 microns before treatment to 529.31 + 17.82 microns after 6 months of treatment. Latanoprost was effective in reducing CCT in 79% of patients. Conclusion: Latanoprost causes a significant reduction in central corneal thickness in patients with primary open angle glaucoma. So it is necessary to measure CCT values regularly in those patients. الهدف: دراسة تأثير اللاتانوبروست موضعياً على ثخانة القرنية المركزية، وهل هناك ضرورة لمراقبة ثخانة القرنية المركزية بشكل دوري عند هؤلاء المرضى. المرضى والطرائق: ضمت العينة 19 مريضاً من مراجعي العيادة العينية في مشفى تشرين الجامعي باللاذقية والأسد الجامعي سابقاً باللاذقية بين كانون الثاني 2016 وكانون الأول 2016. بلغ عدد الذكور 11 والإناث 8. العمر الوسطي 56.1 + 5.08 سنة وتراوحت الأعمار بين 49 و66 سنة. بعد تشخيص الزرق لدى المريض في عين واحدة فقط، تم التقييم بإجراء فحص عيني شامل للعينين بالإضافة لقياس ثخانة القرنية المركزية CCT واختبار شيرمر ومن ثم وصف اللاتانوبروست بشكل قطرة عينية بتركيز 0.005% للعين المصابة فقط. تمت متابعة كل مريض بفواصل شهر، 3 أشهر، و6 أشهر. النتائج: حدث انخفاض هام في متوسط ثخانة القرنية المركزية CCT في مجموعة العيون المصابة من 17.49 + 536.52 ميكرون قبل العلاج إلى 17.82 +529.31 ميكرون بعد 6 أشهر من العلاج. وكان اللاتانوبروست فعالاً في تخفيض CCT عند 79% من المرضى. الخلاصة: يؤدي استعمال اللاتانوبروست عند مرضى الزرق البدئي مفتوح الزاوية لانخفاض هام في ثخانة القرنية المركزية، لذلك فإنه من الضروري مراقبة قيم CCT بشكل دوري عند هؤلاء المرضى.